2016
DOI: 10.20849/aes.v2i1.126
|View full text |Cite
|
Sign up to set email alerts
|

Accelerating Success and Promoting Equity through the Ako: Critical Contexts for Change

Abstract: Achieving equity and excellence for all young people remains the major challenge of education systems across the world. This paper contends that equity and excellence for students currently underserved by our system needs transformative school reform. In response, we outline the ako: critical contexts for change. This model has been applied across five dimensions for transformative reform within Kia Eke Panuku (Note 2).This paper focuses on how this model can be understood and applied alongside curriculum impl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…Adaptive expertise is characterised by innovation and flexibility in the application of knowledge in response to new, diverse, or unique contexts or challenges; in other words, "the ability of educators to respond in flexible, context-sensitive and intelligent ways to novel situations that arise in their work" (Si'ilata, Le Fevre, Ell, Timperley, Twyford, & Mayo, 2015, p. 5). Furthermore, by bringing together adaptive expertise, responsive pedagogy, and strong cultural relationships with both students and their whānau (Berryman and Eley, 2017a;2017b), learning for equity, excellence, and belonging can become a reality for Māori.…”
Section: Responsive Pedagogymentioning
confidence: 99%
“…Adaptive expertise is characterised by innovation and flexibility in the application of knowledge in response to new, diverse, or unique contexts or challenges; in other words, "the ability of educators to respond in flexible, context-sensitive and intelligent ways to novel situations that arise in their work" (Si'ilata, Le Fevre, Ell, Timperley, Twyford, & Mayo, 2015, p. 5). Furthermore, by bringing together adaptive expertise, responsive pedagogy, and strong cultural relationships with both students and their whānau (Berryman and Eley, 2017a;2017b), learning for equity, excellence, and belonging can become a reality for Māori.…”
Section: Responsive Pedagogymentioning
confidence: 99%
“…Many culturalists are calling for a move within classrooms to 'listen to culture' (Bishop & Glynn, 1999;Clark, Smith & Pomare, 1996;Hohepa, 1993;Macfarlane, 2000;Penitito, 1996;cited in Habib et al, 2013, p. 172). Sharon Todd's Toward Imperfect Education (2009) inspires towards the messy, yet healthy, starting place for such a CSEL space, along with many other relevant authors (Andreotti, 2009;Berryman & Eley, 2017;Davies, 1994;de Sousa Santos, 2016;Devine et al, 2012;Jones, 2017;May, 2009). Considering listening and dialogue in such a space links to Freire's Pedagogy of the oppressed (1970,2001).…”
Section: Listening and Dialogical Practicesmentioning
confidence: 99%
“…One of the arguments made for adopting a Tiriti-based approach to education, which brings a Māori approach alongside a Western approach, is that a holistic Māori approach is likely to benefit all learners as well as accelerating learning for groups such as Māori who may have traditionally done poorly within education. In research within a secondary education context, it was found that the holistic Māori approach within Kia Eke Panuku: Building on Success, led to improved outcomes for Māori and non-Māori alike (Berryman & Eley, 2017).…”
Section: Original Articlementioning
confidence: 99%